Pulsed photoacoustic and photothermal response of gold nanoparticles. (21st October 2019) - Kumar, D; Soni, R K; Ghai, Devinder Pal
Abstract: Gold nanospheres and nanorods are promising agents for photoacoustic imaging and photothermal therapy. In this work, seed-mediated methods were optimized for the synthesis of gold nanosphere and nanorod collides of different sizes. Nanosecond pulse photoacoustic and photothermal analysis of these nanoparticles was carried out and compared with finite element simulation. The simulations were performed to quantify the size dependent photoacoustic signal enhancement for nanospheres and nanorods. The non-sphericity contribution of nanospheres was found to enhance the photoacoustic signal. Nanosecond pulse photoacoustic studies of nanorods of different aspect ratio were carried out. Nanorods of aspect ratio ∼4.8 were found to be the most efficient photoacoustic signal generators. Photoacoustic studies of nanorods at varying laser fluence were performed and threshold fluence of 5 mJ cm −2 was observed. Nanorods exposed to nanosecond laser pulses underwent size and shape variations which were confirmed by optical absorbance and transmission electron microscopy measurements. Simulations of nanorods of different aspect ratio and diameter were performed to investigate the photoacoustic signal enhancement and photothermal stability. The miniature size nanorod with a diameter of 10 nm and aspect ratio of 5 was found to be most appropriate in terms of photoacoustic signal generation and photothermal stability.